Education of analgesic Balsam preparation to improve health and family economic revenue for Mabmi Binjai community - De Lux Putra, Effendy; Yuliasmi, Sri; Sri Wahyuni, Henny; Eko Prasetyo, Bayu (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The Indonesian Malay Customary Community (MABMI) is one of the Malay communities in Indonesia, and one of them is located in the city of Binjai, North Sumatra. This organization has many members and is active in carrying out various activities. Members of MABMI in Binjai, who are mostly mothers and elderly (over 60 years old), often complain that they often experience health problems, especially joint pain or muscle pain, which sometimes interfere with their daily life activities. The number of MABMI members in Binjai city who work as housewives, so it is very potential if you want to do entrepreneurial activities at each home so that it can help in improving the family economy. This community service is useful in providing one of the solutions and alternatives for mothers to solve joint health problems that they often experience by providing education and training to make anti-pain balm so that the hope can be used alone if needed. In addition, the team also tried to provide stimulation for mothers who want to do business by developing this anti-pain balm preparation. Education about health products that are safe to use and further information about joint and muscle pain will also be provided by the service team.